Economic Growth, Unemployment, and Education as Determinants of Crime in Jambi Province: A Time-Series Analysis (2013–2022) - Abdul, Wahid; Suherman, Suherman; Nedawati, Rika; Nurdin, Nurdin; Putra, Adi; Pasla, Bambang Niko (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study aims to analyze the impact of economic growth, unemployment, and education on crime rates in Jambi Province during the 2013–2022 period. Background Problems: Crime is not merely the result of individual behavior, but often reflects structural inequalities and unequal access to economic and educational opportunities. Despite the increasing importance of crime prevention in regional planning, empirical research at the provincial level in Indonesia—especially Jambi—is still limited. Novelty: This study contributes by using updated time-series data and focusing specifically on Jambi Province, which remains underrepresented in existing empirical literature on crime determinants in Indonesia. Research Methods: A quantitative approach was applied using multiple linear regression analysis. The study used secondary data obtained from the Central Statistics Agency (BPS) of Jambi Province, covering the period 2013–2022. Finding/Results: All three variables—economic growth, unemployment, and education—have a significant negative effect on crime rates. Among them, unemployment and education were found to be the most dominant factors influencing crime reduction. Conclusion: Efforts to reduce crime in Jambi Province should focus on improving access to education and reducing unemployment. Balanced and inclusive development policies that integrate economic and social aspects are key to building a safer society.